2020
DOI: 10.1002/2211-5463.12849
|View full text |Cite
|
Sign up to set email alerts
|

LCK expression is a potential biomarker for distinguishing primary central nervous system lymphoma from glioblastoma multiforme

Abstract: Glioblastoma multiforme (GBM) and primary central nervous system lymphoma (PCNSL) are both malignant cerebral tumors; however, their treatments are vastly different. Early and precise diagnosis is vital for subsequent adequate treatment to improve prognosis. Reliable biomarkers that can easily distinguish GBM and PCNSL are urgently needed. We evaluated the diagnostic potential of lymphocyte‐specific protein tyrosine kinase (LCK) as a biomarker in differentiating PCNSL from GBM using established computational a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…LCK was expressed at a high level in primary central nervous system lymphoma patients but at a low level in GBM patients. However, LCK expression positively correlated with the levels of infiltrating B cells in diffuse large B-cell lymphoma and GBM [132].…”
Section: Lck Inhibitorsmentioning
confidence: 94%
See 1 more Smart Citation
“…LCK was expressed at a high level in primary central nervous system lymphoma patients but at a low level in GBM patients. However, LCK expression positively correlated with the levels of infiltrating B cells in diffuse large B-cell lymphoma and GBM [132].…”
Section: Lck Inhibitorsmentioning
confidence: 94%
“…It is involved in T-cell receptor signaling, also playing a crucial role in mediating B-cell receptor signaling in chronic lymphocytic leukemia cells. Furthermore, its expression was detected in several neural tissues, including hippocampus, cerebellum, and retina [132].…”
Section: Lck Inhibitorsmentioning
confidence: 99%
“…The role of these proteins in tumor progression is not entirely understood. Nonetheless, most of these proteins have been implicated in the oncogenesis and developmental process of gliomas (Mills et al, 2011;Ge et al, 2020;Li et al, 2020;Moriconi et al, 2021).…”
Section: Cluster Analysismentioning
confidence: 99%
“…Other studies showed that Lck functions as a therapeutic target in acute myeloid leukaemia (AML) [53][54][55] . A recent study showed that Lck was expressed at a high level in primary central nervous system lymphoma (PCNSL) patients 56 . Lck expression was also detected in cholangiocarcinoma 57,58 , breast cancer 12,13,59,60 , colon cancer 14,15,61,62 , and lung carcinoma 16,62,63 .…”
Section: Lck-related Diseasesmentioning
confidence: 99%